Change of seizure frequency in pregnant epileptic women. Issue 8 (August 1983) - Schmidt, D; Canger, R; Avanzini, G; Battino, D; Cusi, C; Beck-Mannagetta, G; Koch, S; Rating, D; Janz, D
Abstract : The effect of pregnancy on seizure frequency was monitored prospectively in 136 pregnancies of 122 epileptic women. Pregnancy did not influence the seizure frequency in 68 pregnancies (50%). In 50 pregnancies (37%) the number of seizures increased during pregnancy or puerperium. The seizure frequency decreased in 18 pregnancies (13%). In 34 out of 50 pregnancies (68%) the increase was associated with non-compliance with the drug regimen or sleep deprivation. In seven out of 18 pregnancies (39%) improvement was related to correction of non-compliance or sleep deprivation during the pregestational nine months. Insufficiently low plasma concentrations of antiepileptic drugs were found in 47% of the women with uncontrolled epilepsy during pregnancy. The course of epilepsy during pregnancy is primarily influenced by non-compliance, sleep deprivation during pregnancy, and inadequate therapy before and during pregnancy. With good medical attention pregnancy itself seems to have only a minimal influence on the course of epilepsy.